Efektivitas Penggunaan Aplikasi Flexible Authentic Survey Instrumen Harmony Mobile dalam Pelayanan Publik untuk mewujudkan E-Government pada Badan Pusat Statistik - Sofian, Iwan; Saifullah, Saifullah (Institut Ilmu Sosial dan Manajemen Stiami, 2025)
This research examines the use of the FASIH Mobile application for data collection, which still encounters several obstacles, such as the manual assignment process, the unavailability of media for monitoring and evaluating data collection results, and the absence of regulations related to the use of this application. This study aims to evaluate the use of the FASIH Mobile application in data collection, identify the obstacles faced and efforts to overcome them. The theory used refers to the effectiveness indicators by Sutrisno. This research uses a qualitative method with a descriptive approach through interview techniques, observation, and documentation studies. Based on the results of the research, the program understanding indicator is effective because the parties involved have understood the purpose and objectives of the application. The timeliness indicator is effective, because the data collection time is in accordance with the schedule listed in the guidebook. The target accuracy indicator is also effective, because the target users of the application are experienced enumerators. The indicators of achieving goals, however, are not considered effective because there are no internal rules or regulations related to the use of the FASIH Mobile application and it has not been integrated with the data processing webentry. Indicators of real change are effective, because the existence of this application eliminates the document entry process. From the research results, it was concluded that the obstacles in using the FASIH Mobile application include the absence of location tagging facilities, limited human resources, and the absence of system integration. Efforts that have been made include evaluating data collection wages using FASIH Mobile and preparing a panel system for system integration. In terms of public services, the use of the FASIH Mobile application improves services in terms of responsiveness which allows data processing and data provision to be faster.